The role of mitochondria-associated ER membranes in disease pathology: protein complex and therapeutic targets - Zhang, Jin; Li, Dan; Zhou, Lingjie; Li, Yanying; Xi, Qian; Zhang, Liuyun; Zhang, Juan (Frontiers in Cell and Developmental Biology, 2025)
The dynamic interactions among organelles play a crucial role in facilitating various intercellular functions, with the interaction between the endoplasmic reticulum (ER) and mitochondria being acknowledged as a prominent example of an interorganellar system. Numerous studies have established that the majority of proteins located at the physically tethered regions between the mitochondria and ER, referred to as mitochondria-associated ER membranes (MAMs), play a crucial role in intracellular physiological processes. MAMs are dynamic membrane coupling regions arising from the interaction between the ER and the outer mitochondrial membrane (OMM). MAMs regulate many biological processes, such as Ca2+ transport, lipid metabolism, and mitochondrial dynamics. A recent study has demonstrated that the proteins associated with MAMs are crucial for both the structural integrity and functional capabilities of the MAMs. Dysregulations in the MAMs proteins are implicated in the onset and progression of various associated diseases, including cancer, neurodegenerative disorders, diabetes mellitus, and cardiovascular diseases. In this review, we provide a comprehensive overview of the protein complex associated with MAMs. We examine its involvement in the pathological mechanisms underlying these diseases, focusing on its functional roles. Additionally, we evaluate and consider the potential of MAMs as therapeutic targets for these diseases.